RATIONAL EMOTIVE BEHAVIOUR THERAPY distinctive features. - Dryden, Windy ([S.l.] : ROUTLEDGE, 2021)
Rational emotive behaviour therapy (REBT) encourages the client to focus on their emotional problems in order to understand and change the rigid and extreme attitudes that underpinthese problems. Following on from the success of the first and second editions, this accessible guide introduces the reader to REBT while indicating how it is different from other approaches within the cognitive-behavioural therapy spectrum. Divided into two sections, the Distinctive Theoretical Features of REBT and the Distinctive Practical Features of REBT, this book presents concise information in 30 key points. Updated throughout, this new edition of Rational Emotive Behaviour Therapy: Distinctive Features will be invaluable to both experienced clinicians and those new to the field.
OCLC-licensed vendor bibliographic record.
Keywords: Rational emotive behavior therapy; PSYCHOLOGY / Cognitive Psychology; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Movements / Behaviorism